2012
DOI: 10.1051/0004-6361/201219041
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of binary stars in the Pleiades with high contrast and spatial resolution

Abstract: Context. It is widely recognized that binarity is a very common feature during star formation; however, different regions and clusters display significantly different binary fractions. This appears to be related to the initial density of the star forming region. The Pleiades cluster has been shown to have a binary fraction similar to that of field stars in the solar neighborhood. Aims. We have taken advantage of a passage of the Moon over the Pleiades cluster, to investigate at high angular resolution two smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Binary stars in clusters can be identified by their overluminosity (Stauffer 1984;Rubenstein & Bailyn 1997;Khalaj & Baumgardt 2013;Sheikhi et al 2016), lunar occultation (Richichi et al 2012), radial velocity techniques (Neill Reid & Mahoney 2000) or by direct imaging (Bouvier et al 1997;Patience et al 2002;Garcia et al 2015;Hillenbrand et al 2018). However these studies are typically limited to relatively close separations with only the direct imaging surveys going out to separations of a few hundred AU.…”
Section: Introductionmentioning
confidence: 99%
“…Binary stars in clusters can be identified by their overluminosity (Stauffer 1984;Rubenstein & Bailyn 1997;Khalaj & Baumgardt 2013;Sheikhi et al 2016), lunar occultation (Richichi et al 2012), radial velocity techniques (Neill Reid & Mahoney 2000) or by direct imaging (Bouvier et al 1997;Patience et al 2002;Garcia et al 2015;Hillenbrand et al 2018). However these studies are typically limited to relatively close separations with only the direct imaging surveys going out to separations of a few hundred AU.…”
Section: Introductionmentioning
confidence: 99%
“…There are no observations of HII-2147 in the literature that resolve the pair, although several attempts have been made at both optical and near-infrared (NIR) wavelengths (Bouvier et al 1997;Metchev & Hillenbrand 2009;Mason et al 2009), including a lunar occultation observation by Richichi et al (2012).…”
Section: Adaptive Optics Imagingmentioning
confidence: 99%
“…In the Pleiades cluster, 34 binary systems (including 2 pairs that were observed twice and identified as binaries of each other, making 32 unique pairs) were found among 212 targets. HII 1306, a 0.60 separation and ∆m opt =0.58 m system was also identified as a binary by Richichi et al (2012), who reported separation 0.65 and ∆m K =0.33 m . HII 134, a 1.84 separation and ∆m opt =0.27 m system was also identified as a binary by Bouvier et al (1997), who reported separation 1.83 and ∆m K =0.13 m .…”
Section: The Pleiades At 136 Pcmentioning
confidence: 99%
“…Notably, the majority of their newly resolved systems had been identified previously as photometric binary candidates (Raboud & Mermilliod 1998a). Richichi et al (2012) identified several Pleiades binaries from lunar occulation observations. In Praesepe, Bettis (1975), Jaschek (1976), and Pinfield et al (2003) identified photometric binary candidates in this cluster as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation